Organophosphate Flame Retardants in Indoor Dust in the Tampa Bay (Florida) Area - Adebayo Solanke; Lukasz Talalaj; Claire Graham; Henry Alegria (Toxics)
As polybrominated diphenyl ethers were phased out as flame retardants and plasticizers, increasing quantities of organophosphate triesters (OPEs) have been used as replacements. Despite a surge in reports on levels and profiles of OPEs, especially in indoor environments, and the potential exposure, there are still understudied areas with no data on the levels of these chemicals. We carried out the first study investigating levels and profiles of OPEs in indoor dust from such an area, the Tampa Bay (Florida) area. ∑13OPEs measured at each site ranged from 545 to 502,086 ng g−1, with overall medians and means over 64 sites of 15,447 and 36,135 ng g−1, respectively. Alkyl OPEs were predominant, with lesser levels of chlorinated and aryl OPEs. Median levels were highest for tris (2-butoxyethyl) phosphate (TBOEP) and triphenyl phosphate (TPHP) at 4641 and 1046 ng g−1, respectively; lower for tris(1,3–dichloro-2-propyl) phosphate (TDCIPP), tris(2-chloropropyl) phosphate (T2CPP), and tris (2-chloroisopropyl) phosphate (TCIPP) at 530, 458, and 360 ng g−1, respectively; with others ranging from 2 to 85 ng g−1. There were differences in levels in different microenvironments (urban versus suburban; non-residential versus residential; apartments versus single-family homes; daycares versus residences and university rooms; building age; and rooms with different floor material). Estimated daily intakes for median and higher exposure scenarios for ∑13OPEs (in ng kg−1 bw day−1) were 12 and 552 for toddlers and 6 and 451 for adults, respectively. TBOEP accounted for 30% of total intake for toddlers and adults in a mean exposure scenario but 90% for high exposure scenario.